(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Model experiments were conducted to estimate the spatial variability of the wind field and carbon dioxide fluxes at different levels over a highly heterogeneous forest area in the Lyalsky Nature Reserve in the Republic of Komi, Russia (62°16’28" N, 50°39’54" E). Calculations were performed using a three-dimensional, Reynolds-averaged Navier-Stokes (RANS) hydrodynamic model of greenhouse gas transport. Lidar measurements of vegetation and topography from unmanned aerial vehicles, chamber measurements of CO2 fluxes near the soil surface, and ERA5 reanalysis data were used as input parameters for the model. The model experiment results showed significant spatial variability of the wind field and CO2 fluxes within and above the forest canopy. This variability is determined by surface topography roughness and vegetation mosaic structure. Comparing the simulated fluxes with the fluxes measured using the eddy covariance method at a long-term monitoring station revealed good agreement between the model calculations and the measurement results in the area adjacent to the station. However, significant spatial variability of vertical fluxes within the model area makes extrapolating point flux measurements to the entire study area problematic.